Implikasi Spiritualitas Yesus sebagai Dasar Integritas bagi Guru Pendidikan Agama Kristen - Muskita, Mesak; Stevanus, Kalis (STTI Harvest Semarang, 2025)
The focus of this article is to highlight the integrity of Jesus and his relationship with His spirituality, especially in the Gospel of Luke. The author will conduct a narrative study of the texts in the Gospel of Luke and combine it with a literature study to get a complete picture of the integrity and spirituality of Jesus. The findings obtained were that Jesus' integrity stemmed from his spirituality, which was demonstrated by his intense prayer activities. Meanwhile, His integrity is demonstrated by His daily life consistent with what He taught. What He taught, that is what He lived. It is hoped that through the results of this research, Christian Religious Educators will not only gain new insights but also be committed to implementing their implications in carrying out their calling as educators. AbstrakFokus tulisan ini adalah menyoroti integritas Yesus dan hubungannya dengan spiritualitas-Nya terutama di dalam Injil Lukas. Penulis akan melakukan kajian naratif terhadap teks-teks di dalam Injil Lukas dan menggabungkan dengan kajian pustaka untuk mendapatkan gambaran yang utuh tentang integritas dan spiritualitas Yesus. Temuan yang diperoleh bahwa integritas Yesus bersumber dari spiritualitas-Nya, yang ditunjukkan dengan aktivitas doanya yang intens. Sedangkan integritas-Nya ditunjukkan dengan kehidupan-Nya sehari-hari konsisten dengan apa Dia ajarkan. Apa yang diajarkan, itulah yang dihidupi-Nya. Guru Pendidikan Agama Kristen diharapkan melalui hasil penelitian ini bukan sekadar memeroleh wawasan baru tetapi komitmen menerapkan implikasinya dalam menjalankan panggilannya sebagai seorang pendidik.